Methylome Dynamics of Bovine Gametes and in vivo Early Embryos - Duan, Jingyue Ellie; Jiang, Zongliang Carl; Alqahtani, Fahad; Mandoiu, Ion; Dong, Hong; Zheng, Xinbao; Marjani, Sadie L.; Chen, Jingbo; Tian, Xiuchun Cindy (Frontiers in Genetics, 2019)
DNA methylation undergoes drastic fluctuation during early mammalian embryogenesis. The dynamics of global DNA methylation in bovine embryos, however, have mostly been studied by immunostaining. We adopted the whole genome bisulfite sequencing (WGBS) method to characterize stage-specific genome-wide DNA methylation in bovine sperm, immature oocytes, oocytes matured in vivo and in vitro, as well as in vivo developed single embryos at the 2-, 4-, 8- and 16-cell stages. We found that the major wave of genome-wide DNA demethylation was complete by the 8-cell stage when de novo methylation became prominent. Sperm and oocytes were differentially methylated in numerous regions (DMRs), which were primarily intergenic, suggesting that these noncoding regions may play important roles in gamete specification. DMRs were also identified between in vivo and in vitro matured oocytes, suggesting environmental effects on epigenetic modifications. In addition, virtually no (less than 1.5%) DNA methylation was found in mitochondrial DNA. Finally, by using RNA-seq data generated from embryos at the same developmental stages, we revealed a weak inverse correlation between gene expression and promoter methylation. This comprehensive analysis provides insight into the critical features of the bovine embryo methylome, and serves as an important reference for embryos produced in vitro, such as by in vitro fertilization and cloning. Lastly, these data can also provide a model for the epigenetic dynamics in human early embryos.